Uczenie się i nauczanie słownictwa języka polskiego za pomocą technologii informacyjnokomunikacyjnych. Stan realizacji projektu „Polish Your Polish/(Un)Polish Your Russian” na KU Leuven (Belgia) - Toffel, Sandra; Van Heuckelom, Kris (Postscriptum Polonistyczne, 2020)
The article presents and evaluates lexical exercises and glottodidactic tasks presented on an educational platform Polish Your Polish – (Un)Polish Your Russian (KU Leuven, Belgia). It is based on the latest scientific literature on using digital educational materials in teaching foreign languages. The analysis proves that the value of the materials prepared at KU Leuven results above all from their authenticity, primacy of the meaning and their attractiveness. When teaching Polish vocabulary using information and communication technologies, it is far more difficult to meet the criteria of effectiveness and functionality. The authors of the article claim that open, multistage tasks, that require active processing of information and lead to a certain useful ‘final’ product can serve this purpose well.